Answer:
z= -1
Explanation:
Simplifying
z + (z + -6) + -2 = -10
Reorder the terms:
z + (-6 + z) + -2 = -10
Remove parenthesis around (-6 + z)
z + -6 + z + -2 = -10
Reorder the terms:
-6 + -2 + z + z = -10
Combine like terms: -6 + -2 = -8
-8 + z + z = -10
Combine like terms: z + z = 2z
-8 + 2z = -10
Solving
-8 + 2z = -10
Solving for variable 'z'.
Move all terms containing z to the left, all other terms to the right.
Add '8' to each side of the equation.
-8 + 8 + 2z = -10 + 8
Combine like terms: -8 + 8 = 0
0 + 2z = -10 + 8
2z = -10 + 8
Combine like terms: -10 + 8 = -2
2z = -2
Divide each side by '2'.
z = -1
Simplifying
z = -1